2014
DOI: 10.1097/mpa.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

“High-Risk Stigmata” of the 2012 International Consensus Guidelines Correlate With the Malignant Grade of Branch Duct Intraductal Papillary Mucinous Neoplasms of the Pancreas

Abstract: The number of high-risk stigmata correlated significantly with the grade of malignancy of BD-IPMNs. The presence of at least 1 high-risk stigma in patients with BD-IPMNs indicates a need for pancreatectomy with lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…There was no stepwise increase in rates of malignant or invasive IPMN with the number of WFs. A recent study published by Aso et al in 2014 reported that the likelihood of malignant BD-IPMN increased in accordance with the number of high-risk stigmata, 9 whereas the number of WF was not significantly correlated with malignancy. In our study, patients with only one predictive factor according to ICG guidelines had a malignancy rate of 15%.…”
Section: Discussionmentioning
confidence: 94%
“…There was no stepwise increase in rates of malignant or invasive IPMN with the number of WFs. A recent study published by Aso et al in 2014 reported that the likelihood of malignant BD-IPMN increased in accordance with the number of high-risk stigmata, 9 whereas the number of WF was not significantly correlated with malignancy. In our study, patients with only one predictive factor according to ICG guidelines had a malignancy rate of 15%.…”
Section: Discussionmentioning
confidence: 94%
“…Patients who have "worrisome features" and additional high-risk signs should also undergo resection, while patients with "worrisome features" alone should receive careful follow-up. The "high-risk stigmata" of IPMNs that can be detected by endoscopic ultrasonography (EUS) are an enhancing solid component inside the cyst and dilation of the main pancreatic duct (>10 mm) [3,[8][9][10][11] . Additional high-risk signs among the "worrisome features" are a definite mural nodule and suspected main duct involvement [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging modalities like CT and MRI remain the first line of investigations in the majority of patients with an expanding body of literature backing this practice. [4][5][6][7][8][9][10] EUS has been suggested to be the most reliable tool for the characterization of IPMNs. 11 The ICG 2012 recommends possible EUS-FNA for evaluation of small BD-IPMNs without WF only in centers with expertise in EUS-FNA and cytological interpretation.…”
Section: Introductionmentioning
confidence: 99%